Billolivia tichii (Gesneriaceae), a new species from Vietnam - Vũ, Ngọc Long; Phạm, Hữu Nhân; Nguyễn, Thế Văn; Luu, Hong Truong (Phytotaxa, 2015)
The genus Billolivia D.J.Middleton in Middleton et al. (2014a: 255) of the Gesneriaceae was recently established with five species, namely B. longipetiolata (Middleton et al. 2014a: 256), B. minutiflora (Middleton et al. 2014a: 258), B. poilanei (Middleton et al. 2014a: 260), B. vietnamensis (Middleton et al. 2014a: 261) and B. violacea (Middleton et al. 2014a: 262). The sixth taxon of the genus, B. moelleri, was described shortly after in Middleton et al. (2014b: 189). Our continued search for the genus in southern Vietnam has gathered several other possible new taxa that are under examination. In this paper, we describe one of them as a new species from Bidoup-Núi Bà National Park.